2014
DOI: 10.1038/srep03737
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of defect migration kinetics in nanoporous Ag with enhanced radiation tolerance

Abstract: Defect sinks, such as grain boundaries and phase boundaries, have been widely accepted to improve the irradiation resistance of metallic materials. However, free surface, an ideal defect sink, has received little attention in bulk materials as surface-to-volume ratio is typically low. Here by using in situ Kr ion irradiation technique in a transmission electron microscope, we show that nanoporous (NP) Ag has enhanced radiation tolerance. Besides direct evidence of free surface induced frequent removal of vario… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…Such remarks have been supported by in-situ ion irradiation experiments of Fe by Prokhodtseva et al [43] and Yao et al [27]. Rapid absorption of individual dislocation loops by free surfaces is also observed during in-situ Kr ion irradiation on nanoporous Ag, and the image force on discrete dislocation loops adjacent to free surfaces provides the driving force for its migration towards free surfaces [40].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Such remarks have been supported by in-situ ion irradiation experiments of Fe by Prokhodtseva et al [43] and Yao et al [27]. Rapid absorption of individual dislocation loops by free surfaces is also observed during in-situ Kr ion irradiation on nanoporous Ag, and the image force on discrete dislocation loops adjacent to free surfaces provides the driving force for its migration towards free surfaces [40].…”
Section: Discussionmentioning
confidence: 69%
“…5(a) shows the loop depth effects of a prismatic 1=3〈1120〉ð1120Þ dislocation loop within ð1120Þ thin foil and a basel 1=20001ð0001Þ dislocation loop within (0001) thin foil. The r ¼ 5 nm dislocation loop is situated at d ¼ 2, 5,10,15,20,25,30,35,40,45 and 48 nm from the bottom surface of the t ¼ 50 nm thin foil, respectively. Anisotropic infinite stress of the dislocation loop is calculated by using Mura's dislocation segment integration formulas [30], and the corresponding anisotropic image displacement fields are calculated with the method of Wu et al [2,28] in Fourier space.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Free surfaces are the strongest known defect sinks and nanoporous metals have shown superior radiation tolerance [22,23]. A recent research showed helium-implanted Ni 73 P 27 metallic glass nanocylinders exhibit enhanced ductility without sacrifice in yield and ultimate tensile strength [24].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous phenomena have been observed using the in situ irradiation technique, such as anisotropic void formation in Mg, [26] irradiation-induced grain growth in Fe and Zr, [27] defect absorption by triple junctions in nanocrystalline Ni, [28] defect removal by twin boundaries (TBs) and the irradiation-induced TB migrations in nanotwinned metals, [29,30] and defect migration kinetics in nanoporous metals. [31][32][33] Meanwhile several in situ mechanical testing studies on irradiated materials are also available. [34,35] Most prior studies on multilayers focused on thin films (several µ m in thickness), whereas the application in nuclear reactors typically calls for bulk nanocomposites.…”
mentioning
confidence: 99%